2020
DOI: 10.2147/opto.s235167
|View full text |Cite
|
Sign up to set email alerts
|

<p>Subjective Comparison of Pre-Lens Tear Film Stability of Daily Disposable Contact Lenses Using Ring Mire Projection</p>

Abstract: Purpose: To subjectively evaluate the in vivo tear film stability of three daily disposable contact lenses (DDCLs) using placido ring reflection at lens wear times of 5 mins and 8 and 12 hrs. Patients and Methods: This prospective, randomized, observer-masked, 3-way crossover study evaluated 28 subjects with good tear film stability. In vivo tear film stability was assessed for three DDCLs (nelfilcon A, etafilcon A, omafilcon A) on three different days over 12 hrs of lens wear. Time to first distortion by non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Muller et al attempted measuring tear film stability using NIK-DUT, which was a method based on the conventional NIKBUT technique. 34 NIK-DUT was recorded from the blink until the appearance of the first distortion of the ring mire by using a stopwatch and not automatic detection. They concluded that although NIK-DUT did not differ significantly among three types of silicone hydrogel SCLs, their subjective wettability grades differed significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Muller et al attempted measuring tear film stability using NIK-DUT, which was a method based on the conventional NIKBUT technique. 34 NIK-DUT was recorded from the blink until the appearance of the first distortion of the ring mire by using a stopwatch and not automatic detection. They concluded that although NIK-DUT did not differ significantly among three types of silicone hydrogel SCLs, their subjective wettability grades differed significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The comfort and vision results were reported previously. 38 There were no adverse events during the study.…”
Section: Resultsmentioning
confidence: 88%
“…Although subjective evaluation was able to determine the first noticeable ring distortion and grade wettability, this procedure is very time consuming in practice. 38 The objective approach may reduce the time necessary to evaluate the captured information. Future studies can evaluate new endpoints that better account for the dynamics of the pre lens tear film and that are not limited to a certain time point as in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations